6+4y(3+5)=

Simple and best practice solution for 6+4y(3+5)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6+4y(3+5)= equation:


Simplifying
6 + 4y(3 + 5) = 0

Combine like terms: 3 + 5 = 8
6 + 4y(8) = 0

Reorder the terms for easier multiplication:
6 + 4 * 8y = 0

Multiply 4 * 8
6 + 32y = 0

Solving
6 + 32y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 32y = 0 + -6

Combine like terms: 6 + -6 = 0
0 + 32y = 0 + -6
32y = 0 + -6

Combine like terms: 0 + -6 = -6
32y = -6

Divide each side by '32'.
y = -0.1875

Simplifying
y = -0.1875

See similar equations:

| -30/3 | | -41+11= | | Y=5x^2+10-3 | | 14/35=24/x | | x82+y4=1/3 | | a^2+10a+22=0 | | 8(4j-4)=-5j-32 | | (x-13)=(2x-1) | | f(x)=9x+1 | | -3/5=y-1/3 | | (2y+x)=(2y-x) | | 42+.05a=42+.08a | | 7=34+x/6 | | -.25x=-8 | | (4x)+(2y-x)=(2y+x) | | 2/3x+6+1/2x+1/4x | | -8/2x+2 | | 4(3x-2)=2(6x+10) | | -2*2X= | | -m/8=9 | | 6(2)+r(2)=(3+r)(2) | | 13-2(4x-5)=7 | | w+13.3=-6.8 | | -3b=6 | | 8y+6=54 | | -6y-6=10+3y+2y | | w+13.6=-6.8 | | 7-n(2a-6)=11 | | x-7.1=-3.8 | | 4x(5+6x)=440 | | 6(x-1)+2=3x+3(-1+x) | | 4y-2y=11 |

Equations solver categories